FARMLAND ACCESS AND INTERGENERATIONAL FARM TRANFER AMONG COCOA FARMERS IN SOUTH- WEST, NIGERIA (Universitas Andalas, 2023)
The study focused on the farmland access and intergenerational farm transfer among cocoa farmers in South-west, Nigeria. The objectives of the study were to investigate cocoa farmers ‘accessibility to land holdings, determine cocoa farmers’ perceived timing of intergenerational farm transfer among others. A multistage sampling procedure was used to select 342 cocoa farmers. The data were collected through interviewer administered questionnaire and analysed using descriptive statistics and multinomial logistic regression. Results showed that majority of the respondents were male (77.0%), having farm size of 5 ha and below (84.9%), the mean age of the respondents was 58 years while the mean household size was 6. The result shows that majority (89.6%) of the respondents had access to their cocoa farmland by purchase, perceived timing of intergenerational farm transfer plan is after the farmer‘s demise (72.2%) and preferred their son (86.4%) to be their successor. However, alternate plan for those who have not identified a successor preferred to sell off (45.6%) the farm. The highest ranked constraint to farmland access was high cost of land with the mean = 2.89. Result shows positive correlation between respondents ‘age (r =0.222, p =0.000), farm size (r= 0.051, p=value 0.000), and access to farmland. The study concluded that cocoa farmers had access to their farmland by purchase with majority having not identifying possible successor. The study recommended that relevant stakeholders should create awareness and train cocoa farmers on the need to identify and engage possible successors early in order to ensure family farm sustainability.